Clinical findings of patients with cystic fibrosis according to newborn screening results - Gursoy, Tugba Ramasli; Aslan, Ayse Tana; Asfuroglu, Pelin; Eyuboglu, Tugba Sismanlar; Cakir, Erkan; Cobanoglu, Nazan; Ozdogan, Sebnem (Wiley, 2022)
Background Cystic fibrosis (CF) is a lethal recessive genetic disease caused by loss of function associated with mutations in the CF trans-membrane conductance regulator. It is highly prevalent (approximately 1 in 3,500) in Caucasians. The aim of this study was to compare demographic and clinical features, diagnostic tests, treatments, and complications of patients with CF whose newborn screening (NBS) with twice-repeated immune reactive trypsinogen testing was positive, normal, and not performed. Methods In this study, 359 of all 1,488 CF patients recorded in the CF Registry of Turkey in 2018, who had been born through the process of NBS, were evaluated. Demographic and clinical features were compared in patients diagnosed with positive NBS (Group 1), normal (Group 2), or without NBS (Group 3). Results In Group 1, there were 299 patients, in Group 2, there were 40 patients, and in Group 3, there were 20 patients. Among all patients, the median age at diagnosis was 0.17 years. The median age at diagnosis was higher in Groups 2 and 3 than in Group 1 (P = 0.001). Fecal elastase results were higher in Group 2 (P = 0.033). The weight z-score was lower and chronic Staphylococcus aureus infection was more common in Group 3 (P = 0.017, P = 0.004, respectively). Conclusions Frequency of growth retardation and chronic S. aureus infection can be reduced with an early diagnosis using NBS. In the presence of clinical suspicion in patients with normal NBS, further analyses such as genetic testing should be performed, especially to prevent missing patients with severe mutations.
Keywords: clinical features; cystic fibrosis; immunoreactive trypsinogen; newborn screening; sweat chloride test